The sisters of reckoning - Davis, Charlotte Nicole (Tor Teen, 2021)
In an alternate Old West, the Good Luck Girls reunite to undertake a wildly ambitious plan to free all dustbloods who live as prisoners to Arketta's landmasters and debt slavery.